Physiological quality and economic evaluation of treated cowpea seeds stored in different packaging (Research, Society and Development, 2020)
The objective of this work was to evaluate the physiological quality of cowpea seeds and the economic viability of storage in different types of packaging and with different chemical treatments. Seeds were submitted to one of the following chemical treatments of active ingredients: fipronil; fipronil + pyraclostrobin + thiophanate methyl; and fludioxonil + metalaxyl. Seeds without chemical treatment constituted the control. Seeds were placed in permeable cotton bags, permeable raffia bags, semipermeable kraft paper bags, and impermeable PET bottles. The following were evaluated: seed moisture content; germination test; first germination count; germination speed index; hypocotyl length; root length and hypocotyl dry mass and root dry mass. Cost analysis of treatments was also performed. The physiological quality of cowpea seeds was more markedly reduced under storage conditions in permeable packages with fludioxonil + metalaxyl treatment. Impermeable packaging without chemical treatment decreased deterioration of physiological quality in cowpea seeds and is economically viable for a storage period of up to 90 days.